Repositioning Village Laws: A Strategic Imperative for Strengthening Local Autonomy - Baskoro, Aji; Rahmatika, Fyna; Wulandari, Andini Firohmatika (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2025)
The implementation of Law Number 12 of 2011 concerning the Formation of Legislation in Indonesia has inadvertently led to the exclusion of village regulations from the national legislative hierarchy. This exclusion has diminished the legal standing of village regulations, thereby undermining the principles of village autonomy. This study, employing a qualitative juridical-normative approach, investigates the urgent need to reposition village regulations within the legislative hierarchy to strengthen local governance and autonomy. Through an analysis of legal documents, academic literature, and relevant legislation, this research identifies three primary justifications for the repositioning of village regulations. Firstly, the formulation process of village regulations reflects the democratic norms and procedures employed by higher levels of government, indicating their inherent legitimacy. Secondly, the authority of village governments to establish norms through regulations constitutes a vital expression of regional autonomy at the grassroots level. Thirdly, the demonstrated effectiveness of village regulations in local implementation underscores their practical significance in community governance. These findings, supported by historical, sociological, and juridical evidence, highlight the urgency of restoring village regulations to their rightful place within the legislative hierarchy. This repositioning is essential not only for bolstering village autonomy but also for promoting effective and responsive governance at the local level, ultimately contributing to a more robust and decentralized governance framework in Indonesia.